2016
DOI: 10.18632/oncotarget.10669
|View full text |Cite
|
Sign up to set email alerts
|

miR-7 reverses the resistance to BRAFi in melanoma by targeting EGFR/IGF-1R/CRAF and inhibiting the MAPK and PI3K/AKT signaling pathways

Abstract: MicroRNAs (miRNAs) are attractive therapeutic targets for various therapy-resistant tumors. However, the association between miRNA and BRAF inhibitor resistance in melanoma remains to be elucidated. We used microarray analysis to comprehensively study the miRNA expression profiling of vemurafenib resistant (VemR) A375 melanoma cells in relation to parental A375 melanoma cells. MicroRNA-7 (miR-7) was identified to be the most significantly down-regulated miRNA in VemR A375 melanoma cells. We also found that miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 46 publications
3
77
0
Order By: Relevance
“…An increasing body of literatures documented that miR-7 could regulate the growth of lung cancer cells though various signal pathways such as the Akt and Erk pathway 27, 28, 29. Our previous work also showed that miR-7 could inhibit the proliferation and metastasis of lung cancer cells though the Akt pathway 17 .…”
Section: Resultsmentioning
confidence: 87%
“…An increasing body of literatures documented that miR-7 could regulate the growth of lung cancer cells though various signal pathways such as the Akt and Erk pathway 27, 28, 29. Our previous work also showed that miR-7 could inhibit the proliferation and metastasis of lung cancer cells though the Akt pathway 17 .…”
Section: Resultsmentioning
confidence: 87%
“…To our knowledge, this is the first report of a miRNA enriched along the EEC lineage trajectory that exerts substantive control of enteroid growth and likely EEC abundance. Although previously miR-7 has been reported to have roles in specific cancer contexts, 17,29,30 our study is the first to our knowledge to demonstrate that miR-7 regulates intestinal growth under normal physiological conditions. It is noteworthy that modest but significant changes in miRNA expression, similar to what we show for miR-7 in this study, have been linked functionally to important phenotypes in numerous prior studies.…”
Section: Discussionmentioning
confidence: 57%
“…Introduction of miR-7 decreases the expression levels of EGFR, IGF-1R, CRAF in vitro as well as in Vemurafenib-resistant cells in melanoma xenograft mice models, which indicates that EGFR, IGF-1R, and CRAF are the target genes of miR-7 that are associated with the acquired resistance to BRAFi. By decreasing the expression levels of EGFR, IGF-1R, CRAF, miR-7 could inhibit the activation of the MAPK and PI3K/AKT pathways and reverse melanoma cell resistance to BRAFi [25].…”
Section: Mirnas Acting As Oncosuppressors In Melanomamentioning
confidence: 99%